2021
DOI: 10.1037/per0000491
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of personality functioning in ICD-11 posttraumatic stress disorder and complex posttraumatic stress disorder.

Abstract: The newly added diagnosis complex posttraumatic stress disorder (CPTSD) in the 11th edition of the International Classification of Diseases (ICD-11) includes a domain of disturbances in self-organization (DSO), in addition to PTSD. The DSO construct appears to have definitional overlap with the dimensional personality pathology severity measure, personality functioning. This study investigated the association between personality functioning and ICD-11 CPTSD, and the associations between DSO clusters and person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…It was even suggested that Criterion A closely aligns with the so-called general factor of psychopathology included in the alternative nosology of mental disorders, the Hierarchical Taxonomy of Psychopathology (HiTOP) [ 11 , 28 , 29 ]. Nonetheless, this could also consequently lead to difficulties with differential assessment between personality disorders and other mental disorders, because many of them can fulfill the diagnostic threshold as well [ 26 ]. This can be important especially when using the ICD-11, where the emphasis is primarily on characterizing personality functioning problems, and description using trait domain qualifiers is rather voluntary [ 5 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was even suggested that Criterion A closely aligns with the so-called general factor of psychopathology included in the alternative nosology of mental disorders, the Hierarchical Taxonomy of Psychopathology (HiTOP) [ 11 , 28 , 29 ]. Nonetheless, this could also consequently lead to difficulties with differential assessment between personality disorders and other mental disorders, because many of them can fulfill the diagnostic threshold as well [ 26 ]. This can be important especially when using the ICD-11, where the emphasis is primarily on characterizing personality functioning problems, and description using trait domain qualifiers is rather voluntary [ 5 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internal consistency, measured by McDonald’s ω, was high in our sample (total = 0.936, Self = 0.898, Interpersonal = 0.89). In our study, in addition to the total severity score, we use the two domain scores – Self and Interpersonal functioning – and twelve facets scores as well (as already done by previous studies exploring personality functioning [ 26 , 27 ]).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations